IMPLEMENTASI TANGGUNG JAWAB ORANG TUA TERHADAP ANAK PASCA PERCERAIAN PERSPEKTIF UU No. 16 TAHUN 2019 - Mohammad Faizin; Syarifa Febrilia (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This study aims to analyze the implementation of parental responsibility towards children after divorce, the legal basis for child protection, and the impact of divorce on child welfare. The research method used is a normative juridical approach with a literature study technique through the assessment of laws and regulations, the Compilation of Islamic Law, court decisions, as well as relevant literature and previous research results. The results of the research show that the obligations of parents after divorce include the fulfillment of financial support, custody (hadhanah), education, and the physical and psychological protection of children. However, in practice, the implementation of these obligations still faces various obstacles, such as low legal awareness among parents, prolonged conflicts, and weak enforcement of court decisions. The suboptimal implementation of parental responsibilities has an impact on the psychological, social, educational, and economic conditions of children. This study concludes that the welfare of children after divorce is more determined by the consistency of the implementation of parental responsibilities than by the marital status of the parents. Therefore, synergy between parents, judicial institutions, the state, and society is needed to ensure the protection and fulfillment of children's rights after divorce.